(untitled) (South Asian Journal of Agriculture, 2022)
Routine use of antibiotics in poultry production leads to its residues in meats and eggs and multi-drug resistance develops in human gut due to consumption of contaminated products. The study was conducted with a view to investigate the effect of probiotic supplementation to the poultry ration as an alternative to antibiotics on the performance of broilers. The experimental broilers were divided in four groups according to the treatments as control (no antibiotics or probiotics supplementation), AS20 (antibiotics supplementation @20g 100kg-1 of feed), PS10 (probiotics supplementation @10g 100kg-1 of feed) and PS20 (probiotics supplementation @20g 100kg-1 of feed). The experiment was laid out at Dr. Purnendu Gain Field Laboratory of Agrotechnology Discipline, Khulna University, Khulna by following Completely Randomized Design (CRD) with 4 replications for the treatments and 15 birds were included in each replication. The generic name of antibiotic used was oxytetracycline and trade name of probiotic was probiolac which contains a combination of several microorganisms of 32 billion CFU100g-1. Results revealed that the performances of broilers in terms of body weight gain, feed intake, feed conversion ratio, feed cost and mortality rate varied insignificantly due to antibiotics and probiotics supplementation. Numerically, highest mortality was recorded in antibiotics supplemented group and no mortality observed in control and probiotic (@20g 100kg-1 of feed) fed group. Significant positive correlation was observed among feed intake, body weight, feed conversion ratio and growth rate of the chicks. It could be concluded that probiotic can be supplemented as an alternative to antibiotic in broiler ration. South Asian J. Agric., 8(1&2): 45-50